A fluorescent ESIPT-based benzimidazole platform for the ratiometric two-photon imaging of ONOO−in vitro and ex vivo. Issue 28 (30th June 2020) - Odyniec, Maria L.; Park, Sang-Jun; Gardiner, Jordan E.; Webb, Emily C.; Sedgwick, Adam C.; Yoon, Juyoung; Bull, Steven D.; Kim, Hwan Myung; James, Tony D.
Abstract : In this work, we have developed an ESIPT benzimidazole-based platform for the two-photon cell imaging of ONOO − and a potential ONOO − -activated theranostic scaffold. Abstract : In this work, we have developed an ESIPT-based benzimidazole platform (MO-E1 and MO-E2 ) for the two-photon cell imaging of ONOO − and a potential ONOO − -activated theranostic scaffold (MO-E3 ). Each benzimidazole platform, MO-E1–3, were shown to rapidly detect ONOO − at micromolar concentrations (LoD = 0.28 μM, 6.53 μM and 0.81 μM respectively). The potential theranostic MO-E3 was shown to release the parent fluorophore and drug indomethacin in the presence of ONOO − but unfortunately did not perform well in vitro due to low solubility. Despite this, the parent scaffold MO-E2 demonstrated its effectiveness as a two-photon imaging tool for the ratiometric detection of endogenous ONOO − in RAW264.7 macrophages and rat hippocampus tissue. These results demonstrate the utility of this ESIPT benzimidazole-based platform for theranostic development and bioimaging applications.